PERLUASAN ASAS LEGALITAS DALAM RKUHP SEBAGAI UPAYA PEMBAHARUAN HUKUM PIDANA INDONESIA - Pradiva, I Gusti Ngurah Bayu; Hariyanto, Diah Ratna Sari (Kertha Semaya : Journal Ilmu Hukum, 2022)
Tujuan studi ini yakni guna mengidentifikasi serta mengerti latar belakang perluasan makna asas legalitas dalam RKUHP serta memahami apakah perluasan asas legalitas dalam RKUHP tidak bertentangan dengan makna dari asas legalitas itu sendiri. Riset ini memanfaatkan jenis riset hukum normatif, pendekatan statute approach, pendekatan historis, serta pendekatan sosiologis. Hasil riset memperlihatkan bahwa perubahan esensi asas legalitas yang mencakup asas legalitas materiel tersebut sebenarnya merupakan wujud dari semangat untuk mengubah KUHP warisan kolonial Belanda dengan hukuman pidana yang lebih sejalan dengan prinsip-prinsip luhur bangsa Indonesia. Perluasan makna asas legalitas dalam RKUHP dapat menimbulkan benturan dan pertentangan namun, hal itu dapat diatasi dengan peran dari Pemerintah Daerah setempat dengan mengeluarkan Peraturan Daerah dengan memasukan unsur pidana adat di dalamnya, sehingga mampu untuk mengefektifkan penerapan asas legalitas materiel yang sejalan dengan prinsip-prinsip yang terdapat pada UUD 1945, Pancasila, HAM, serta asas hukum umum yang diterima oleh khalayak umum. The purpose of this study is to identify and understand the background of the expansion of the meaning of the legality principle in the RKUHP and to understand whether the expansion of the legality principle in the RKUHP does not conflict with the meaning of the legality principle itself. This research utilizes the types of normative legal research, the statute approach, the historical approach, and the sociological approach. The results of the research show that the change in the essence of the principle of legality which includes the principle of material legality is actually a manifestation of the spirit to change the KUHP inherited from the Dutch colonial with criminal penalties that are more in line with the noble principles of the Indonesian nation. The expansion of the meaning of the principle of legality in the RKUHP can cause conflicts and contradictions, however, this can be overcome by the role of the local government by issuing a regional regulation that includes elements of customary law in it, so as to be able to effectively implement the principle of material legality in line with the principles laid down. contained in the 1945 Constitution, Pancasila, Human Rights, and general legal principles accepted by the general public.